Isolation and Genomic Characterization of Avian Reovirus From Wild Birds in South Korea - Kim, Sang-Won; Choi, Yu-Ri; Park, Jong-Yeol; Wei, Bai; Shang, Ke; Zhang, Jun-Feng; Jang, Hyung-Kwan; Cha, Se-Yeoun; Kang, Min (Frontiers in Veterinary Science, 2022)
Avian reoviruses (ARVs) cause severe arthritis, tenosynovitis, pericarditis, and depressed growth in chickens, and these conditions have become increasingly frequent in recent years. Studies on the role of wild birds in the epidemiology of ARVs are insufficient. This study provides information about currently circulating ARVs in wild birds by gene detection using diagnostic RT-PCR, virus isolation, and genomic characterization. In this study, we isolated and identified 10 ARV isolates from 7,390 wild birds’ fecal samples, including migratory bird species (bean goose, Eurasian teal, Indian spot-billed duck, and mallard duck) from 2015 to 2019 in South Korea. On comparing the amino acid sequences of σC-encoding genes, most isolates, except A18-13, shared higher sequence similarity with the commercial vaccine isolate S1133 and Chinese isolates. However, the A18-13 isolate is similar to live attenuated vaccine av-S1133 and vaccine break isolates (SD09-1, LN09-1, and GX110116). For the p10- and p17-encoding genes, all isolates have identical fusion associated small transmembrane (FAST) protein and nuclear localization signal (SNL) motif to chicken-origin ARVs. Phylogenetic analysis of the σC nucleotide and amino acid sequences revealed that all isolates were belonged to genotypic cluster I. For the p10- and p17-encoding genes, the nucleotide sequences of all isolates indicated close relationship with commercial vaccine isolate S1133 and Chinese isolates. For the σNS-encoding genes, the nucleotide sequences of all isolates indicated close relationship with the Californian chicken-origin isolate K1600657. Our data indicates that wild birds ARVs were derived from the chicken farms. This finding suggests that wild birds serve as natural reservoirs of such viruses for domestic poultry